Faktor-faktor yang Berhubungan dengan Perilaku Ibu Hamil dalam Pemeriksaan HIV di Wilayah Kerja Puskesmas Halmahera Kota Semarang - Yunida Halim; Syamsulhuda BM; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
HIV/AIDS is a health problem throughout the world, including Indonesia. HIV is becoming an increasing concern in Indonesia, particularly among women of reproductive age. In Semarang city until June 2016 HIV cases in housewives reached 1503 cases and 297 cases in children. Therefore, efforts should be made to prevent HIV transmission from mother to child through HIV testing during pregnancy. The purpose of the research to analyze the factors related with maternal behavior to hiv testing in the region of halmahera health center, semarang. This research used quantitative method with cross sectional approach, with 60 population and 54 samples by using total sampling, 6 person dropout. Data were analyzed using chi square test (significant level is 0,05). The result showed that pregnant women do HIV testing as much as 74,1% and 25,9% do not conduct examination. Result of statistical test show several factors related with maternal behavior to hiv testing are knowledge (0,001) attitude (0,002), availability of facilities and infrastructure (0,001) and support of health workers (0,020). While factors do not related with maternal behavior to hiv testing are age (0,652), educational level (0,550), works (1,000), support of husband (0,111) and support of family (0,256). Effort that need to done is approach from health worker to pregnant women and family in the provision of information related to prevention and the transmission of hiv from mother to child. Promoting the services room means that privacy and comfortable to keep confidentiality.